Altruistic responses to the most vulnerable involve sensorimotor processes - Vickers, Brian D.; Seidler, Rachael D.; Stansfield, R. Brent; Weissman, Daniel H.; Preston, Stephanie D. (Frontiers in Psychiatry, 2023)
Introduction Why do people help strangers? Prior research suggests that empathy motivates bystanders to respond to victims in distress. However, this work has revealed relatively little about the role of the motor system in human altruism, even though altruism is thought to have originated as an active, physical response to close others in immediate need. We therefore investigated whether a motor preparatory response contributes to costly helping. Methods To accomplish this objective, we contrasted three charity conditions that were more versus less likely to elicit an active motor response, based on the Altruistic Response Model. These conditions described charities that (1) aided neonates versus adults, (2) aided victims requiring immediate versus preparatory support, and (3) provided heroic versus nurturant aid. We hypothesized that observing neonates in immediate need would elicit stronger brain activation in motor-preparatory regions. Results Consistent with an evolutionary, caregiving-based theory of altruism, participants donated the most to charities that provided neonates with immediate, nurturant aid. Critically, this three-way donation interaction was associated with increased BOLD signal and gray matter volume in motor-preparatory regions, which we identified in an independent motor retrieval task. Discussion These findings advance the field of altruism by shifting the spotlight from passive emotional states toward action processes that evolved to protect the most vulnerable members of our group.